2019
DOI: 10.5230/jgc.2019.19.e36
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy Improves Survival in Gastric Signet-Ring Cell Carcinoma: a SEER Database Analysis

Abstract: PurposeTo identify the potential therapeutic role of postoperative radiotherapy (RT) in patients with locally advanced (stage II and stage III) gastric signet ring cell carcinoma (SRC).Materials and methodsPatients with locally advanced gastric SRC from the Surveillance, Epidemiology, and End Results program database between 2004 and 2012 were included in our study. Univariate and multivariate Cox proportional models were performed, and survival curves were generated to evaluate the prognostic effect of postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…27 Wei's study reported that postoperative radiotherapy can provide a better survival in locally advanced GSRC patients (HR = 0.788, 95% CI: 0.64, 0.94). 26 This result provides the evidence for application of adjuvant RT on treatment of GSRC patients. In our study, we offer an alternative and effective treatment of adjuvant CRT for GSRC patients by analyzing the recent nationwide survey data.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…27 Wei's study reported that postoperative radiotherapy can provide a better survival in locally advanced GSRC patients (HR = 0.788, 95% CI: 0.64, 0.94). 26 This result provides the evidence for application of adjuvant RT on treatment of GSRC patients. In our study, we offer an alternative and effective treatment of adjuvant CRT for GSRC patients by analyzing the recent nationwide survey data.…”
Section: Discussionmentioning
confidence: 53%
“…25 As the same, Wei et al reported that postoperative chemotherapy did not improve survival (HR = 0.935, 95% CI: 0.674, 1.296) in 859 stage II-III GSRC patients. 26 Another study from Shi et al showed that survival benefits (HR = 0.28, 95% CI: 0.24, 0.32) of postoperative chemotherapy in 2815 stage IV GSRC patients. 27 Wei's study reported that postoperative radiotherapy can provide a better survival in locally advanced GSRC patients (HR = 0.788, 95% CI: 0.64, 0.94).…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, a study by Wei et al demonstrated that postoperative chemotherapy did not provide a dramatic survival benefit in 1303 GSRC patients (HR=0.935, 95% CI: 0.674, 1.296). 44 Additionally, postoperative chemotherapy did not show a positive impact on survival in the 144 GSRC patients from Li's study (HR=0.654, 95% CI: 0.271, 1.581). 45 It appears that only Shi et al suggested that a selected group of stage IV GSRC patients benefited from postoperative chemotherapy (HR = 0.61, 95% CI: 0.51-0.73).…”
Section: Postoperative Chemotherapymentioning
confidence: 83%
“…46 Nonetheless, from the perspective of Wei, postoperative radiotherapy provided more possibilities for survival (HR=0.788, 95% CI: 0.644, 0.009) of patients with locally advanced GSRC. 44 Most previous studies did not offer compelling evidence on this issue. Therefore, more randomized controlled trials are required in further studies.…”
Section: Radiotherapymentioning
confidence: 99%
“…Besides, tumor sidedness was divided into left-sided colon (including splenic flexure, descending colon, sigmoid colon and rectosigmoid cancers) and right-sided colon (including cecum, ascending colon, hepatic flexure and transverse colon) 12 , 15 , 22 , 23 . Age and tumor size were grouped in accordance with prior researches 24 , 25 . In addition, the staging of cancer is based on the 6th edition of AJCC stage system, which adapted to patients in the SEER database with from 2004 to 2015.…”
Section: Methodsmentioning
confidence: 99%